Pan-ebolavirus protective therapy by two multifunctional human antibodies - Gilchuk, Pavlo; Murin, Charles D.; Cross, Robert W.; Ilinykh, Philipp A.; Huang, Kai; Kuzmina, Natalia; Borisevich, Viktoriya; Agans, Krystle N.; Geisbert, Joan B.; Zost, Seth J.; Nargi, Rachel S.; Sutton, Rachel E.; et al. (Cell, 2021)
Ebolaviruses cause a severe and often fatal illness with the potential for global spread. Monoclonal antibody-based treatments that have become available recently have a narrow therapeutic spectrum and are ineffective against ebolaviruses other than Ebola virus (EBOV), including medically important Bundibugyo (BDBV) and Sudan (SUDV) viruses. Here, we report the development of a therapeutic cocktail comprising two broadly neutralizing human antibodies, rEBOV-515 and rEBOV-442, that recognize non-overlapping sites on the ebolavirus glycoprotein (GP). Antibodies in the cocktail exhibited synergistic neutralizing activity, resisted viral escape, and possessed differing requirements for their Fc-regions for optimal in vivo activities. The cocktail protected non-human primates from ebolavirus disease caused by EBOV, BDBV, or SUDV with high therapeutic effectiveness. High-resolution structures of the cocktail antibodies in complex with GP revealed the molecular determinants for neutralization breadth and potency. This study provides advanced preclinical data to support clinical development of this cocktail for pan-ebolavirus therapy. [Display omitted] •Two human antibodies recognize different conserved sites on ebolavirus glycoproteins•The cocktail exhibits broad neutralizing activity and resists viral escape in vitro•Antibodies synergize to neutralize virus and differentially engage their Fc regions•The therapeutic cocktail protects NHPs against three medically important ebolaviruses A broad-spectrum therapeutic antibody treatment against medically important ebolaviruses is not available but highly desirable. Gilchuk et al. report a therapeutic cocktail comprising two broadly neutralizing human antibodies that exhibit synergistic neutralizing activity, complementary Fc region-mediated effector functions, resistance to viral escape, and protection of non-human primates from disease caused by Ebola, Bundibugyo, or Sudan ebolaviruses with high effectiveness and also define the structural basis for neutralization breadth and potency by this cocktail.